The effect of ethical digital governance based educational management on the managerial readiness of madrasah ibtidaiyah teachers - Sulfa Potiua; Wadan Y Anuli (Jurnal Prima Edukasia, 2026)
Digital educational management in Madrasah Ibtidaiyah (MI) in North Sulawesi faces challenges related to ethical security and data integrity amid the rapid expansion of artificial intelligence (AI). This study examines the relationship between Ethical Digital Governance (EDG) based educational management and teachers’ managerial readiness. Using a quantitative correlational design, data were collected from 524 MI teachers through a five point Likert questionnaire developed from the POAC framework (Planning, Organizing, Actuating, and Controlling). Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results show a statistically significant positive relationship between EDG and managerial readiness (R = 0.361; R² = 0.13; p < 0.05), indicating that EDG explains 13% of the variance in readiness. Although the correlation is weak, the positive direction suggests that strengthening ethical standards and digital transparency supports teachers’ psychological safety and pedagogical autonomy. Teachers demonstrate responsible AI use; however, institutional control remains largely compliance-oriented, potentially contributing to technostress. EDG therefore functions as a foundational enabling factor rather than a dominant predictor of managerial readiness. Future research should incorporate additional structural and competency-based variables to better explain managerial preparedness in Islamic educational institutions.